Radiological screening of impacted wisdom teeth in HUSM - Tangaya, Mr. Davendran s/o (2016)
Introduction Impacted third molars are developmental pathologic medical deformities characteristic of a modem civilization. Impaction of third molars is seldom found in medieval populations. It is well established that radiographs are an important diagnostic input for assessing and treatment planning of the dental patient, whether symptomatic or asymptomatic. Radiography does in most instances provide more information with regards to the impacted third molars than clinical examination alone, especially of the very important relationship between the roots of the mandibular third molar and the mandibular canal. Aim The aim of this research study is to evaluate the four selected types of radiographs; Skull X-ray, Paranasal Sinuses X-ray, TMJ X-ray and mandible X-ray which is believed could give the maximum possible coverage of the wisdom teeth presence, if any, its impaction and its surroundings. From this evaluation then, the association for the presence of wisdom tooth or impacted wisdom tooth with other parameters governing it (gender, age, caries, orientations and angulations) is found out. Also the frequency of these parameters is evaluated to compare the diagnostic present of wisdom teeth in each type of radiograph. This is done, to give an answer for the question whether the selected radiological views will provide any valuable information. Material and methods A series of 4 different approaches of extra-oral radiographs of different procedures from HUSM radiology archives involving as many as 50 samples for each type of imaging involving; P A of skull, TMJ, paranasal sinuses, and mandible radiographs views was selected. The collective data was then transfers to SPSS versionll.O for statistical analysis. Results For the testing of association, there is a very highly significant association between the age group of patients and the presence of wisdom tooth in the skull imaging. Other that, it is ·also found that there is a significant association between the gender and presence of wisdom tooth in the mandible imaging. Expect for both of this association, all other testing of association gave non significant association or relationship. Where else for the testing of frequency, there is few notable, high frequencies were observed. Off this, it is found that most of the impacted tooth in this research study was those of unerupted impacted wisdom tooth with the mean value of 34.9%. Then, it is also noted that, the mesioangulation type of impaction is the most observed type of impaction in this study with a mean value of68.1%. Finally, with 87.3% mean value for the presence of caries on wisdom tooth, it is understood that there is very low probability of caries presence on wisdom tooth. Conclusions Holistic radiological imaging of the wisdom tooth requires integration of scientific knowledge based on anatomical-radiological-clinical close linkage and clinical professionalism based on awareness and competence of the subject thus leading to unprecedented knowledgeable health sciences teamwork.